Theories, technologies and practices of exploration and development of volcanic gas reservoirs: A case study of Cretaceous volcanic rocks in Songnan fault depression - MA Daixin,REN Xianjun,ZHAO Mifu,HAN Jiaoyan,LIU Yuhu (Youqicang pingjia yu kaifa)
In the past two decades, Sinopec Northeast Oil & Gas Company has made significant strides in exploring the southern Songliao Basin, revealing that the basin's volcanic rocks present a new and promising avenue for hydrocarbon exploration. According to the exploration practice of the basin, the company has developed a comprehensive four-component coupling reservoir control model specific to fault depressions. This model emphasizes the interconnected evolution of key elements such as hydrocarbon generating foci, reservoir formation periods, paleostructure, fault cap preservation, and effective reservoirs, with a particular focus on the main accumulation period. This strategic approach led to the significant discovery of a large-scale volcanic gas reservoir within the Huoshiling Formation in the Changling fault depression, located in the Songnan area. Consequently, the exploration focus has broadened from the Yingcheng Formation to the Huoshiling Formation, diversifying the exploration targets from acidic volcanic rocks to intermediate-basic volcanic rocks, and extending from subaerial to submarine eruptions. By using the technique of fine gas reservoir description, the integration of modeling, numerical modeling and geological engineering, the productivity breakthrough has been achieved in several wells in Songnan fault depression, and the efficient development and large-scale production of volcanic gas reservoir has been realized.